Pengaruh Fasilitas Belajar Siswa Terhadap Hasil Belajar Matematika Siswa di Kelas X SMAN 5 Bukittinggi - Chantika, Dilla; Ramdhani, Vivi; Aniswita, Aniswita; Firmanti, Pipit (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research is motivated by the difference in learning facilities and student learning outcomes in class X of SMAN 5 Bukittinggi. Many students are found with high learning facilities, but the learning outcomes are not very satisfactory, and some are even below the KKM. The purpose of the study is to determine the significant influence between learning facilities on the mathematics learning outcomes of students in class X of SMAN 5 Bukittinggi for the 2022/2023 Academic Year. This type of research is correlation research. The population in this study is 334 students in class X with a sample of 33 students. The sampling technique uses a simple random sampling technique. The data collection technique used is in the form of a questionnaire to find out the learning facilities at home and tests to obtain data on learning outcomes. The data analysis technique used linear regression equations, correlation coefficients, simple determination coefficients, and the significance of correlation coefficients. The results of the study were obtained from tcount  ttable, which is 2,252  1,696 which means that learning facilities have a significant effect on learning outcomes. Where learning facilities have an effect of 79.3% on mathematics learning outcomes. Where between the two variables there is a positive correlation of 0.35, with the regression equation obtained is Y= 22.8046+0.590X